Representasi Pesan Dakwah pada Film How To Make Millions Before Grandma Dies - Hamandia, Muhammad Randicha; Hertimi, Sri; Marizka, Refi (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2025)
This study aims to reveal the representation of the message of da'wah in the film How to Make Millions Before Grandma Dies through Roland Barthes' semiotic approach. This film was chosen because although it does not explicitly carry a religious theme, it implies relevant Islamic da'wah values, such as compassion, sincerity, reflection on life, and devotion to parents. The research method used is qualitative descriptive with semiotic analysis techniques that include three main stages: denotation, connotation, and myth. The results of the study show that this film contains da'wah messages in three aspects: faith, sharia, and morals. The message of faith is depicted in the understanding of death as the destiny of Allah SWT; sharia appears through sincerity in keeping promises; and morals are seen in the attitude of respect for parents and sincere affection. Thus, this film is able to become an alternative media for da'wah that is effective and emotionally touching, especially for the younger generation.